Treatment protocol for abnormal uterine bleeding in reproductive age from the perspective of Persian medicine - Mojgan Tansaz; Masoumeh Norouzi Allahleh Korabi; Marzieh Qaraaty; Roshanak Mokaberinejad; Nafiseh Zafarghandi; Morteza Mojahedi (Mashhad University of Medical Sciences, 2023)
Introduction: Abnormal uterine bleeding occurs as a disturbance in the quantity, duration, regularity and schedule of menstruation, which has been a significant problem. The present study was performed with aim to summarize the recommendations of Persian medicine in the treatment and management of abnormal uterine bleeding. Methods: In this narrative review article, the key words related to abnormal uterine bleeding (AUB) in the sources of Persian medicine, which is called "Efrate tams", were reviewed and the items related to nutritional measures and treatment of this disease were extracted. Keywords "Menorrhagia" or "Menometrorrhagia" or "Abnormal uterine bleeding-AUB" or "Poly-menorrhea" or "Herbal medicine" or "Nutritional treatment" and "Efrate tams" were searched in SID, PubMed, Scopus, Web of science, Science direct and Google Scholar databases, and finally the cases which had scientific evidence were presented in the form of nutritional measures and treatment. Results: A significant part of the recommendations of Persian medicine for the treatment of abnormal uterine bleeding has practical clinical evidence. These include the use of foods which reduce bleeding and fast digestion, avoiding the consumption of heavy foods, lifestyle modification, the use of herbal medicines, and also the prescription of appropriate medical treatments according to the patients' conditions. Conclusion: Based on the results of this study, the use of simple solutions of Persian medicine in the treatment of abnormal uterine bleeding along with common medicine protocols can help in controlling this disease and contribute to the health of women as much as possible.